2009
DOI: 10.4103/0250-474x.51958
|View full text |Cite
|
Sign up to set email alerts
|

Various solvent systems for solubility enhancement of enrofloxacin

Abstract: Solubility enhancement of antimicrobial drug enrofloxacin has been studied using a series of co-solvents and surfactants. Aqueous solubility of enrofloxacin could be increased up to 26 times. Co-solvents alone produced only small increase in solubility. However, the combined effect of co-solvents and buffer was synergistic and a large increase in solubility could be attained. Ionic surfactants were found to be much better solubilizing agents than non-ionic surfactant. Amongst ionic surfactants, solubility was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 8 publications
1
36
0
Order By: Relevance
“…transfer of drug from pure water to aqueous solution of solubilizers (Mixed solvents). [23,24] The value of Gibbs free energy for cosolvent and solid colvents was observed in range of -2490.16 to -6820.39 kJ mol −1 , respectively. Saturated solutions of drug were studied for pH dependent solubility at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…transfer of drug from pure water to aqueous solution of solubilizers (Mixed solvents). [23,24] The value of Gibbs free energy for cosolvent and solid colvents was observed in range of -2490.16 to -6820.39 kJ mol −1 , respectively. Saturated solutions of drug were studied for pH dependent solubility at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…For various aqueous formulation blends of mixed solvents (AF1 to AF8) the value of ΔG 0 tr are extremely negatives and the value are observe to decrease as increase in solubilizers concentration, demonstrating spontaneous nature of drug solubilization. [23,24] The structures of drugs and hydrotropes with different centers of different electro negativity might responsible for the intermolecular hydrogen bonding and electrostatic attraction. Hydrogen bonding between the amide group of urea and various negative centers of drug molecule seems to impart aqueous solubility to aceclofenac.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the distribution, free concentration and the metabolism of various drugs may be strongly affected by drugprotein interaction in the blood stream. [4][5][6][7] Therefore, study of the interactions between protein and drug molecules will help provide basic information on the pharmacological actions, biotransformation, bio-distribution, etc. of drugs.…”
mentioning
confidence: 99%